2010
DOI: 10.1002/mrm.22094
|View full text |Cite
|
Sign up to set email alerts
|

Cell tracking using iron oxide fails to distinguish dead from living transplanted cells in the infarcted heart

Abstract: Recently, debate has arisen about the usefulness of cell tracking using iron oxide-labeled cells. Two important issues in determining the usefulness of cell tracking with MRI are generally overlooked; first, the effect of graft rejection in immunocompetent models, and second, the necessity for careful histological confirmation of the fate of the labeled cells in the presence of iron oxide. Therefore, both iron oxide-labeled living as well as dead epicardium-derived cells (EPDCs) were investigated in ischemic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 20 publications
0
54
0
1
Order By: Relevance
“…Hypointensities detected on MRI refer only to iron oxide particles themselves, but cannot give any information on the type or viability of labeled cells. 15 Besides iron particles retained in labeled cells, the persistence of hypointensities may be affected by the imbalance between the massive iron oxide particles released from the dead labeled stem cells and the relatively restricted iron oxide clearance capacity of the brain. 17 It is well known that the iron oxide clearance was mainly through endogenous macrophages/ microglia engulfment, which are then taken away by cerebral blood flow.…”
Section: Duan Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Hypointensities detected on MRI refer only to iron oxide particles themselves, but cannot give any information on the type or viability of labeled cells. 15 Besides iron particles retained in labeled cells, the persistence of hypointensities may be affected by the imbalance between the massive iron oxide particles released from the dead labeled stem cells and the relatively restricted iron oxide clearance capacity of the brain. 17 It is well known that the iron oxide clearance was mainly through endogenous macrophages/ microglia engulfment, which are then taken away by cerebral blood flow.…”
Section: Duan Et Almentioning
confidence: 99%
“…13,14 The ability of SPION-based MRI to reliably evaluate long-term cell engraftment and survival remains controversial. Further studies have shown that long-lasting hypo-signal intensity on MRI mainly originated from macrophages that engulfed SPION, 15,16 or from extracellular iron particles that persisted in the interstitial space after the grafted labeled cells died. 17 However, almost all of these investigations mainly focused on cell fate in myocardial infarction.…”
mentioning
confidence: 99%
“…The released nanoparticles can reside for a long time or be taken up by other cells and thus create a contrast agentrelated signal that is not related to the presence of the transplanted cell itself. 51,71,[110][111][112][113] In the study by Guenoun et al, 71 it was shown that prolonged retention of released cell label is dependent on nanoparticle characteristics. In this study, a comparison was made between iron oxide nanoparticles and Gdliposomes (liposomes containing gadopentetate dimeglumine in the water phase) as cell labelling agents for monitoring the in vivo fate of transplanted cells.…”
Section: Effects Of Nanoparticle Sizementioning
confidence: 99%
“…20 In this study, tumour antigen-containing DCs were labelled with iron oxide nanoparticles or 111 In-oxine and coinjected into lymph nodes of 10 patients with melanoma under ultrasound guidance. The patients subsequently underwent MRI and scintigraphy, by which the labelled DC vaccine could be visualized.…”
Section: Clinically Relevant Insights Gained From Pre-clinical Studiementioning
confidence: 99%
“…Subsequently, macrophages may phagocytose dead cells and iron particles, which may become secondarily iron labeled. 33 Second, cell viability was different after transplantation, which was due to the different injection sites. 34 Finally, although we used PBS to remove loosely attached or extracellular particles, it is possible that a small amount of iron particles was attached to the surface of the labeled cells.…”
Section: Mri Tracking Of Iron Oxide Nanoparticle-labeled Hmscs In Limmentioning
confidence: 99%